Biosynthesis of Silver Nanoparticles Using Garcinia cowa Aqueous Leaf Extract and Their Antifungal Activity Against Durian Dieback Pathogen - Usa Sukkha; Awadol Khejonrak; Phitsamai Kamonpha; Anuchit Ruangvittayanon; Sirichatnach Pakdeepromma; Pornprapa Kongtragoul (My University, 2023)
Silver nanoparticles (AgNPs) were synthesized under different pH and reaction time using the Garcinia cowa aqueous leaf extract. The formation, crystal structure and morphology of synthesized AgNPs were investigated using UV-Vis spectroscopy, X-ray diffraction (XRD) and transmission electron microscopy (TEM) techniques. The UV-Vis result indicated that the AgNPs were synthesized using Garcinia cowa aqueous leaf extract at all pH conditions within 10 min. The synthesis of AgNPs was signifi cantly affected by pH condition which was shown by the TEM micrographs. The particle sizes of AgNPs were in a nano-sized range; 6.30 ± 3.52 nm for pH 4, 3.87 ± 2.51 nm for pH 7 and 13.97 ± 11.84 nm for pH 10. Furthermore, the AgNPs prepared in pH 4, pH 7 and pH 10 (120 min reaction time) at different concentrations were assessed for their antifungal activity against durian dieback pathogen. It was found that the 800 mL/L of AgNPs prepared at pH 7, the smallest particle size and good dispersion, showed the highest inhibition mycelial growth at 47.33%, whereas the larger nanoparticles prepared at pH 4 and pH 10 conditions showed lower inhibition of mycelial growth at 43.22% and 32.55%, respectively.
Keywords: Silver nanoparticle; Natural Compound Pharmacology Studies